MEASURING MARKETPLACE SUCCESS APPROACH DELONE & MCLEAN IS SUCCESS MODEL: A STUDY AMONG STUDENTS - Sambas Ade Kesuma; Eunike Kristina Sinuhaji; Risanty Risanty; Fauziah Kumalasari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the success of marketplace applications using the Delone & McLean model for undergraduate students of Accounting, Faculty of Economics and Business, University of North Sumatra. The variables used are system quality, information quality, and service quality, which are related to the success of marketplace applications, as measured by user satisfaction. This study used a quantitative method with data from 301 respondents analyzed using multiple linear regression. The results showed that simultaneously and partially, all three variables had a positive and significant effect on the success of marketplace applications. This indicates that improving system quality, information quality, and service quality can increase user satisfaction.